The Effectivity of Clonidine Addition to Levobupivacaine 0.25% for Scalp Block in Patients Underwent Craniotomy Surgery - Tjokorda Gde Agung Senapathi (Journal of Global Pharma Technology, 2019)
Background: The scalp nerve block technique is a relatively simple and safe technique. Clonidine is well-known as an agent that extends the analgesia effect of local anesthetic drugs. The goal of this study was to evaluate the effectiveness of clonidine addition as adjuvants in levobupivacaine 0.25% in scalp nerve block in craniotomy procedures. Patients and Methods: This was a clinical trial with a double-blind, randomized study using consecutive sampling technique. Inclusion criteria include patients underwent craniotomy surgery due to brain tumor using general anesthesia with endotracheal tube in 18-60 years of age. As an addition to general anesthesia, group a received levobupivacaine 0.25% and clonidine 2 µg/kg as a regiment for scalp block. Group B received levobupivacaine only for the same purpose. All other treatments were similar for both groups. Results: The intraoperative fentanyl requirement (100 (50-150) vs. 150 (75-200) mcg, p <0.001), the period to the postoperative first PCA dose (822.5±129.7 vs. 387.8±69.6 minutes, p <0.001), and the total need of postoperative morphine by PCA (2.0 (1.0-3.0) vs. 3.0 (2.0-7.0) mg, p <0.001) were lower in the clonidine-added levobupivacaine groups compared to levobupivacaine alone. 3 Conclusions: The addition of clonidine to levobupivacaine 0.25% on scalp block is effective in reducing the need for intraoperative and postoperative opioids, reducing postoperative pain, extending the duration of scalp nerve block, and delaying the first PCA dose.Keywords: Clonidine, Levobupivacaine, Fentanyl, Morphine, Pain, Requirements.